Depressive symptoms and unprotected sex in St. Petersburg, Russia. - Zhan, Weihai; Shaboltas, Alla V; Skochilov, Roman V; Kozlov, Andrei P; Krasnoselskikh, Tatiana V; Abdala, Nadia (Journal of psychosomatic research, 2012)
Growing evidence indicates that emotional distress such as depression may have the potential to increase the risk for HIV and other sexually transmitted infections (STIs). This study investigated the association between depressive symptoms and unprotected sex among STI clinic patients in Russia.
Keywords: Adolescent; Condoms; Depression; Female; Humans; Male; Middle Aged; Risk-Taking; Russia; Sexual Behavior; Unsafe Sex